PENANAMAN KARAKTER DISIPLIN DI MADRASAH IBTIDAIYAH - Fiki Dzakiyyatul Aula; Miftakhur Rizki (LPPM STAI Muhammadiyah Probolinggo, 2022)
The main problem in the character of discipline is the tendency of lack of discipline. Several violations also occurred in the school environment such as being late for class, truancy, not doing assignments, not wearing uniforms according to the rules, and other violations. This is a serious problem because discipline is one of the success factors in learning. This research uses a qualitative method with a case study approach at MI Plus Al-Fataimah Sukorejo Bojonegoro. The primary data sources in this study were the head of the madrasa, the student council, and class teachers starting from grades 1-3. The data collection method used participatory observation, and semi-structured interviews at MI Plus Al-Fatimah Sukorejo Bojonegoro. The data collection process in this study used data analysis techniques from Miles and Hubrman. In the process of cultivating disciplined character, several processes of cultivating disciplined character are carried out through routine school activities, spontaneous activities, and example. First, routine activities carried out according to schedule such as morning apples every Monday, daily picket activities, congregational prayers, asking for permission when leaving class, sending letters to teachers when not attending school, and saying greetings when meeting ustadz and clerics. Second, spontaneous activities carried out by ustadz/ustadzah when students commit commendable attitudes or violations. Third, the teacher's example, the teacher gives a good example to students. Keywords: Character Education, Discipline, Elementary school